(3JTMjf GdJPgjH dcJGH GdJgPjHs - (3GdMLQj, eMeO Hf Ydj Hf SYjO, J (B1199 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; Gddge Ef MeOc CfjSj aj GOdGLj hHYO ajbhd eMeO Hf Ydj Hf SYjO Gf GdhVY GdZQjH GdeQShe HGdJgPjH Ufag GdJaJGRGfj cJGH hbY Ydi JaVjdg GdELeGY aCedjJ dPdc gPg GdMGTjI hSejJgG HJTMjf GdJPgjH TQM cJGH GdJgPjH s
(3BNQgG (B:s
(3cGTaI ddTQM cCfgG djSJ TjFG hQCg ChGf GdbUQ CVGaj Cj dG ZjQg ef GdTQhM dG eWdbG hgPG ZGjI eG CQOfGg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 /296s
(3eYLe GdeDdajf (B3 / 513s
(3EjVGM Gdecfhf (B1/289s
(3gOjI GdYGQajf (B2/345s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs